2010
DOI: 10.1016/j.ejphar.2009.11.053
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic curcuminoid derivative inhibits nitric oxide and proinflammatory cytokine synthesis

Abstract: Curcumin is a highly pleiotropic molecule with significant regulatory effects upon inflammation and inflammatory related diseases. However curcumin has one major important limitation in which it has poor bioavailability. Design of synthetic structural derivatives of curcumin is but one approach that has been used to overcome its poor bioavailability while retaining, or further enhancing, its drug-like effects. We have synthesized a series of curcumin analogues and describe the effects of 2,6-bis-4-(hydroxyl-3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 31 publications
4
32
0
1
Order By: Relevance
“…As described previously, curcumin had some targets, such as growth factors, growth factor receptors, transcription factors, cytokines, enzymes, and apoptosis regulator genes. 38,39,42,43 Gautam and Jachak 44 demonstrated decreased levels of IL-1b and TNF-a in mice suffering from chronic inflammation. By in vitro study, it is shown that a level of 5mM curcumin at can inhibit the production of TNF-a and IL-1 by human monocyte induced by Lipopolysaccharide (LPS).…”
Section: Figurementioning
confidence: 98%
“…As described previously, curcumin had some targets, such as growth factors, growth factor receptors, transcription factors, cytokines, enzymes, and apoptosis regulator genes. 38,39,42,43 Gautam and Jachak 44 demonstrated decreased levels of IL-1b and TNF-a in mice suffering from chronic inflammation. By in vitro study, it is shown that a level of 5mM curcumin at can inhibit the production of TNF-a and IL-1 by human monocyte induced by Lipopolysaccharide (LPS).…”
Section: Figurementioning
confidence: 98%
“…The amount of nitrite was extrapolated from the sodium nitrite (Sigma Aldrich) standard graph. The inhibition rate was calculated as described previously by Tham et al (2010).…”
Section: Nitrite Determinationmentioning
confidence: 99%
“…The protein concentration in the cell lysate was determined using the Pierce Bicinchoninic Acid (BCA) Protein Assay kit (Thermo Fisher Scientific) as described by the manufacturer. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and Western blot were performed as described by Tham et al (2010). To detect iNOS and β-actin, the membranes (Pall Corporation, Port Washington, NY, USA) were incubated separately in antiiNOS rabbit polyclonal primary antibody (1:1000 dilution) (Cayman Chemical Company, Ann Arbor, MI, USA) and anti-β-actin polyclonal antibody (1:1000 dilution) (BioVision Incorporated, Milpitas, CA, USA) overnight.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…There are many attempts to synthesize curcumin analogues to circumvent the problem of low bioavailabilities and extensive metabolism (Anand et al 2007(Anand et al , 2008. In terms of the potential pharmacodynamic effects of curcumin, anti-inflammatory (Tham et al 2010;Zhao et al 2010) and antioxidant activities (Dai et al 2009) are two of the most prominent properties among all others. Interestingly, some analogues have independent anti-inflammatory activities that are not associated with the "antioxidant" activities (Lee et al 2009).…”
Section: Polyphenols: Curcumin and Curcmin Analoguesmentioning
confidence: 99%